The State of Hiring Discrimination: A Meta-Analysis of (Almost) All Recent Correspondence Experiments - Louis Lippens; Siel Vermeiren; Stijn Baert (Institute of Labor Economics (IZA), 2021)
Notwithstanding the improved integration of various minority groups in the workforce, unequal treatment in hiring still hinders many individuals' access to the labour market. To tackle this inaccessibility, it is essential to know which and to what extent minority groups face hiring discrimination. This meta-analysis synthesises a quasi-exhaustive register of correspondence experiments on hiring discrimination published between 2005 and 2020. Using a random-effects model, we computed pooled discrimination ratios concerning ten discrimination grounds upon which unequal treatment in hiring is forbidden under United States federal or state law. Our meta-analysis shows that hiring discrimination against candidates with disabilities, older candidates, and less physically attractive candidates is at least equally severe as the unequal treatment of candidates with salient ethnic characteristics. Remarkably, hiring discrimination against older applicants is even more outspoken in Europe than in the United States. Furthermore, unequal treatment in hiring based on sexual orientation seems to be prompted mainly by signalling activism rather than same-sex orientation in itself. Last, aside from a significant decrease in ethnic hiring discrimination in Europe, we find no structural evidence of recent temporal changes in hiring discrimination based on the various other grounds within the scope of this review.
Keywords: J71; J23; J14; J15; J16; 330; hiring discrimination; unequal treatment; meta-analysis; correspondence experiment; audit study